Tailoring Hydrophobicity of Thioflavin T to Optimize Aβ Fibril Bioimaging - Zunbul, Zehra; An, Jusung; Aziz, Hira; Shin, Jinwoo; Lim, Sungsu; Yu, Le; Kim, Yun Kyung; Kim, Jong Seung (Wiley-VCH, 2023)
Fluorescence imaging of amyloid beta (Aβ) polypeptide using a small-molecule fluorophore is a practical system for Alzheimer's disease (AD) diagnosis in clinical and research fields. Herein, a molecular designing strategy for a new fluorogenic probe that equips bathochromic emission shift and enhanced binding affinity toward Aβ fibril through structural optimization is suggested. Thioflavin T (ThT)-derived fluorescent dyes are developed by adjusting the hydrophobicity of electron donor moiety in D–π–A structures with biannulated ring expansion. Indeed, probes are tuned to have redshifted fluorescence emission wavelength and optimized binding affinities for Aβ fibrils in vitro and cortical imaging. Detection of background signal is minimized by maintaining the photophysical properties of twisted intramolecular charge transfer (TICT), resulting in significantly sensitive fluorogenic probes for outstanding bioimaging in AD.